2005
DOI: 10.1111/j.1468-3156.2005.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with their lives – women, learning disabilities, self‐harm and the secure unit: a Q‐methodological study

Abstract: Deliberate self-harm represents a significant, yet it can be argued, a poorly theorized area of concern with respect to women who have learning disabilities -particularly in the context of secure service provision. Utilizing ideas from social constructionism we explore how some ways of understanding dominate the professional literature and, thereby, restrict how such women can be understood. We recognize that despite this, multiple understandings about why women with learning disabilities self-harm do exist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…Self-harm is a potent medium for communicating and regulating emotions, such as anger. James and Warner [12] and Pembroke [13] agree with this and report that service users sometimes hurt their bodies to release frustration and as a form self-punishment or to avenge others.…”
Section: Introductionmentioning
confidence: 84%
“…Self-harm is a potent medium for communicating and regulating emotions, such as anger. James and Warner [12] and Pembroke [13] agree with this and report that service users sometimes hurt their bodies to release frustration and as a form self-punishment or to avenge others.…”
Section: Introductionmentioning
confidence: 84%
“…(Warner and Wilkins, 2004:267) A small number of studies have looked at experiences of self harm from the point of view of women service users with learning disabilities. James and Warner's (2005) study concluded that judging women against inappropriate male standards would be to additionally penalize them for their self harming behaviour. The patients and staff in their research described self harm as a coping strategy to deal with past traumatic experiences, current relationships and issues around privation and security.…”
Section: Control or Therapy?mentioning
confidence: 99%
“…Women are often believed to contribute to staff stress and burnout due to more frequent incidents of aggression and self harm (Fish, 2000). Research within secure units (Harker-Longton and Fish, 2002;Fish and Culshaw, 2005;James and Warner, 2005;Duperouzel and Fish, 2008;Duperouzel and Fish, 2010) suggests that staff and organisational responses to these types of incident are further distressing to women and viewed as punishments, for example the use of physical restraint and confiscation of belongings to control self-harm.…”
Section: The Institutional Response To Women In Secure Carementioning
confidence: 99%
See 2 more Smart Citations